Students’ Self-Reported Use of AI Chatbots in Vocabulary Learning: A Mixed-Methods Study in A Reading Course - Zakky Yavani; Putri Dhini Apriliani; Khomarudin Khomarudin (MASI Mandiri Edukasi, 2026)
This study examines students’ self-reported integration of AI chatbots into vocabulary learning in the Literacy for Academic Purposes course by reporting on the usage of various vocabulary learning tasks. An explanatory sequential mixed-methods design was adopted. Quantitative data were collected from 82 third-semester English Education students with an 18-item self-reported questionnaire. Descriptive statistics were used for data analysis in IBM SPSS Statistics version 23. The qualitative phase involved semi-structured interviews with six students and one course lecturer, and the interview data were analyzed using the Braun and Clarke thematic analysis. The quantitative data reported that finding meaning in context, generating the meaning of a word, and reading comprehension were the most regularly used AI chatbots, whereas vocabulary consolidation and vocabulary application were reported the least. The qualitative data reported that the study participants mainly used AI chatbots to aid their comprehension of vocabulary while reading and that the study participants used AI chatbots the least to reinforce vocabulary and to engage in the productive use of language. Joint display analysis indicated that AI chatbot use was task-centered, and qualitative data reported the task-specific use of AI chatbots in vocabulary learning tasks. The findings of the study reported that the use of AI chatbots in vocabulary retrieval should be extended to the use of AI chatbots in vocabulary consolidation, the productive use of language, and the critical use of AI chatbots.